Surgical Management of Multiple Myeloma and Plasmocytoma of the Spine - G Evangelisti; E Pesce; R Gala; S Bandiera; G Tedesco; G Barbanti Brodano; S Terzi; R Ghermandi; M Girolami; V Pipola; A Gasbarrini (International Journal of Spine Research - Peertechz Publications, 2020)
Multiple Myeloma (MM) is caused by the neoplastic proliferation of plasma cells that produce monoclonal immunoglobulins in the bone marrow thereby causing skeletal damage. Other MM-related complications include hypercalcemia, renal insufficiency, anaemia, and infections [1].